1976
DOI: 10.1002/ijc.2910170118
|View full text |Cite
|
Sign up to set email alerts
|

Detection of private and common tumor‐associated antigens in murine sarcomas induced by different chemical carcinogens

Abstract: Two fibrosarcomas of similar histological type, induced in C3Hf mice by either methylcholanthrene or 3,4-benz(a)pyrene, were shown to have individually unique tumor-rejection antigens in classical transplantation-type experiments. By contrast, sera of autochthonous mice, which resisted only transplants of the immunizing sarcoma, were found to contain complement-dependent cytotoxic antibodies, specific for both sarcomas, in vitro. The existence of individually unique as well as common tumor-associated antigens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1977
1977
1990
1990

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Subsequent experimentation in highly inbred laboratory animals has firmly established the concept of TAA and, in particular, of "unique" tumour-associated transplantation antigens (TATA) on chemically induced tumours (Foley, 1953;Prehn and Main, 1957;Klein et al, 1960;Old et al, 1962). In vivo studies with chemically induced tumours in the ensuing years have generally confirmed these observations (Baldwin, 1973;Wahl et al, 1974;Forbes, Nakao and Smith, 1975;Fritze et al, 1976). However, in a few studies, shared TATA on chemically induced tumours have also been demonstrated (Koldovsky and Svoboda, 1963;Reiner and Southam, 1967;Robert, 0th and Dumont, 1973).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Subsequent experimentation in highly inbred laboratory animals has firmly established the concept of TAA and, in particular, of "unique" tumour-associated transplantation antigens (TATA) on chemically induced tumours (Foley, 1953;Prehn and Main, 1957;Klein et al, 1960;Old et al, 1962). In vivo studies with chemically induced tumours in the ensuing years have generally confirmed these observations (Baldwin, 1973;Wahl et al, 1974;Forbes, Nakao and Smith, 1975;Fritze et al, 1976). However, in a few studies, shared TATA on chemically induced tumours have also been demonstrated (Koldovsky and Svoboda, 1963;Reiner and Southam, 1967;Robert, 0th and Dumont, 1973).…”
mentioning
confidence: 96%
“…Crossreacting TAA have been detected in vitro both by serological techniques (Harder and McKhann, 1968;Hellstrom, Hellstrom and Pierce, 1968;Tachibana and Klein, 1970;Burdick and Wells, 1973;Fritze et at., 1976) and by assays of cellmediated immunity where lymphoid cells from tumour-bearing or tumour-immune hosts were tested against various tumour cell lines (Hellstrom et al, 1968;Takasugi and Klein, 1970;Bataillon, Ross and Klein, 1975;Forbes et al, 1975;Whitney, Levy and Smith, 1975).…”
mentioning
confidence: 99%
“…Contrary to the high degree of cross-reactivity exhibited at both humoral and cellular levels in chickens (Edelman et al, 1985a.b), chemically induced sarcomas of murine origin frequently express highly immunogenic tumor transplantation antigens which are distinct for each individual tumor. This is shown by the absence, in general, of cross-protection in vivo against fibrosarcomas induced by the same chemical agent in syngeneic mice immunized against one fibrosarcoma (Fritze et al, 1976;Hellstrom et al, 1978;Srivastava et al, 1986;Palladino et al, 1987). Nevertheless, in agreement with the present results, the existence of crossreactivity among tumor transplantation antigens has also been observed among various chemically induced syngeneic tumors in rodents (Hellstrom et al, 1978;Palladino et al, 1987;Leffell and Coggin, 1977;Law, 1984;Chou et al, 1988;Coggin, 1989).…”
Section: Discussionmentioning
confidence: 93%
“…The antigenic cross-reactivity among dif ferent MC-induced sarcomas and of sarco mas with lymphoma and leukemia cells has been previously described [3,4,[17][18][19][20]. This cross-reactivity has been interpreted as being due to embryonal antigens, sharing of 'foreign' H-2 allospecificities, viral antigens or to sharing of tumor-specific antigens [3,[20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…By these tests, antigeneic individuality or cross-reactivity of the tumor-specific anti gens among different chemically induced tu mors has been reported [2][3][4], H-2 allospecificities of these tumors have been studied by either complement-de pendent cytotoxicity techniques in cultured cells or by the absorption of specific alloantisera with these tumors. H-2 alloantigen ex pression on neoplastic cells seems to play a role in tumor immunity mechanisms since new alloantigens can be detected on the surface of these cells and their possible role as tumorspecific antigens has been postulated [5][6][7].…”
Section: Introductionmentioning
confidence: 99%